1993
DOI: 10.1063/1.465733
|View full text |Cite
|
Sign up to set email alerts
|

Binding of radical species to surfaces: Cluster models for OH on Cu(111)

Abstract: The chemisorptive interaction of the hydroxy radical (OH) with the Cu(111) surface and its consequences for the surface electronic structure are studied by CunOH (n ranging from 1 to 25) cluster models using ab initio Hartree–Fock and correlated wave functions. A comparison of the adsorbate binding at the Cu(111) on top, bridge, and the two threefold hollow [face-centered-cubic and hexagonal-close-packed (fcc and hcp)] sites based on extended geometry optimizations yields the fcc site energetically favored wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 34 publications
3
22
0
Order By: Relevance
“…The work functions of Ag(100), Ag(110), and Ag(111) surfaces are 4.61 eV, 4.52 eV, and 4.74 eV [47] respectively. The adsorption behavior of OH on Ag(111) is similar to that on Cu(111) [32] and Ni(111) [29]. All these theoretical studies [29,32] clarified the high-coordinated threefold site as the most stable adsorption site.…”
Section: Oh Adsorption On Ag(111)mentioning
confidence: 84%
See 2 more Smart Citations
“…The work functions of Ag(100), Ag(110), and Ag(111) surfaces are 4.61 eV, 4.52 eV, and 4.74 eV [47] respectively. The adsorption behavior of OH on Ag(111) is similar to that on Cu(111) [32] and Ni(111) [29]. All these theoretical studies [29,32] clarified the high-coordinated threefold site as the most stable adsorption site.…”
Section: Oh Adsorption On Ag(111)mentioning
confidence: 84%
“…OH binds strongly to a clean metal surface and is at 80 K does not result in azimuthal ordering of adsorbed H 2 O on any of the Ag facets, in markpreferentially adsorbed at high-coordination sites in Ni(100) [29], Ni(111) [29][30][31] and Cu(111) ed contrast to the local ordering observed for H 2 O+O on Ni(111) [5]. Adsorbed H 2 O reacts [32]. The valence orbital structure of hydroxyl is characterized by partially filled 1p orbitals, which with preadsorbed oxygen to form OH species that are bonded with the molecular axis perpendicular are similar in shape and energy to the O 2p states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,[11][12][13] Copper-based catalysts are also used in the automobile industry, 14,15 as well as for acrolein synthesis, dehydrogenation of cycloalkanes, and dehydrogenation of alcohols. 14-16 Accordingly, numerous experimental and theoretical studies have been conducted to understand the fundamental surface chemistry of copper, in terms of the adsorption of species such as hydrogen, 17,18 oxygen, [18][19][20] carbon, 21 hydroxyl, 18,22 CO, and NO. 5,20,23 Here, we present a systematic study of the structures and energetics of monatomic (H, O, N, S, and C) and diatomic (CO, NO, and OH) species on Cu(111).…”
Section: Introductionmentioning
confidence: 99%
“…Optimized geometry for the structure S4 in which the 2-chlorophenoxy radical is adsorbed above a 3-fold hollow fcc site and the H at a neighbouring fcc site. [36] radicals, respectively. We have also found that the interatomic distances between the surface copper atoms coordinating the oxygen atom increase by 5.0% and 2.6% from the bulk value of 2.571 Å in S4 and S5, respectively.…”
Section: Dissociative Structures 3221 Formation Of a 2-chlorophenmentioning
confidence: 98%